An Analysis on the Omnibus Law and Its Challenges in Indonesia: The Perspectives of the Constitutional and the Islamic Law - Dwiono, Sugeng; Ja’far, A. Kumedi; Haryadi, Slamet (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
The Omnibus Law, which encompasses the Constitutional Law and the Islamic Law, has been the subject of intense dispute since its inception. The controversy has occurred from the inception to the promulgation of the design process within larger communities. Multiple issues emerged from the outset when the administration introduced the proposal for an Omnibus Law in the Indonesian People's Consultative Assembly of the Republic of Indonesia (DPR RI) to its enactment. This study uses normative legal methodologies, which are examined through the lens of the constitutional law theory and the Islamic law. The study determined that the Omnibus Law is a legislative tool commonly employed by countries that follow a common law legal system. However, it was subsequently embraced by nations that follow a civil law framework, such as Indonesia. The Omnibus Law was enacted to ensure the efficient and effective execution of laws, particularly in the area of copyright regulations, in order to prevent any duplication or overlap. Consequently, public perceives the law as lacking ambition and instead favoring the concerns of the community, particularly in relation to employee compensation, employment agreements, and the practice of subcontracting. Based on the constitutional law, this state policy is deemed conditionally unlawful, despite the ongoing application of these legal standards by the executive and parliamentary parties. Within the framework of Islamic jurisprudence, it can be regarded as a component of siyasah syar'iyah or governmental strategy that aligns with the principles of maqāṣid al-sharī'ah, particularly hifdz al-mal, which involves preserving economic stability and promoting halal certification. However, this article contends that the judgment of the Constitutional Court to deem it unlawful is contingent. It advocates for a modification of the copyright law pertaining to creative works, with the aim of ensuring broader adherence to legal regulations.